(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Introduction: For the service to be of high quality and please the patient, the patient’s needs and expectations must be addressed. The more closely the service adheres to the wants and demands of the customers, the higher the service quality will be, and the more loyal and satisfied the customers will be. Aims: to evaluate the respondents’ socioeconomic status and the variables affecting their patients’ happiness. Methods: 200 participants were surveyed using planned interviews and observation as part of the current study’s information collection process. Through purposeful sampling, the respondents were selected. Results: The results showed that most respondents were between the ages of 31 to 40 years, male, married, and Hindu. According to research on the effect of healthcare services on patient satisfaction, most respondents agreed that their complaints and problems are handled fairly, that they are happy with their service, and that they have a good relationship with the nurse and other staff. All of the respondents took cost into account when using hospital services.